Effect of cutting regime on soil physical properties of wet thistle meadows - Renata DUFFKOVÁ; Tomáš KVÍTEK (Soil and Water Research, 2009)
Changes of selected soil physical properties (porosity P, soil organic matter SOM, bulk density ρd, particle density ρz, characteristics of water retention capacity - maximum capillary water capacity θCMC, and non-capillary porosity Pn) of permanent grassland (wet, non-fertilized, thistle meadows ass. Angelico-Cirsietum palustris, crystalline complex area, Czech Republic) in the top soil layer (3-10 cm) managed under three regimes (uncut UC; cut once a year C1; cut twice a year C2) were monitored for one undrained and two drained sites. There were no significant differences in selected soil physical properties among the test plots at the beginning of the study. As the intensity of utilisation decreased, the values of P, SOM, and Pn increased and ρd, ρz and θCMC decreased. Within 5-10 years of the beginning of the study, average values were: P at UC = 70, C1 = 69, C2 = 67%; SOM at UC = 10.7, C1 = 10.6, C2 = 10.0%; ρd at UC = 0.76, C1 = 0.79, C2 = 0.84 g/cm3; ρx at UC = 2.53, C1 = 2.55, C2 = 2.56 g/cm3; θCMC at UC = 50, C1 = 53, C2 = 51%; Pnat UC = 21, C1 and C2 = 16%. Moderate negative dependence of both ρx and ρd on SOM and of ρd on Pn and a moderate positive dependence of P on SOM was observed. θCMC changes did not show links to other soil physical properties. The greatest looseness of the top soil layer, expressed by a decrease in ρd, occurred with the UC regime in direct correlation with SOM, Pn and P.